Structural trends in a series of bulky dialkylbiarylphosphane complexes of CuI. Issue 9 (17th August 2021) - Woodhouse, Sidney S.; Buchanan, Jenna K.; Dais, Tyson N.; Ainscough, Eric W.; Brodie, Andrew M.; Freeman, Graham H.; Plieger, Paul G.
Abstract : Six Cu I complexes containing 2‐di‐ tert ‐butylphosphanyl‐2′, 4′, 6′‐triisopropylbiphenyl ( t BuXPhos) and an ancillary ligand were prepared and characterized. A weaker interaction between the metal and ancillary ligand was observed to result in a stronger copper–arene interaction. Abstract : Cu I complexes containing the bulky dialkylbiarylphosphane 2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl ( t BuXPhos, L ) and an ancillary ligand (Cl −, Br −, I −, MeCN, ClO4 − or SCN − ) have been structurally characterized, namely, chlorido[2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ]copper(I), [CuCl(C29 H45 P)], 1, bromido[2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ]copper(I), [CuBr(C29 H45 P)], 2, [2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ]iodidocopper(I), [CuI(C29 H45 P)], 3, (acetonitrile‐κ N )[2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ]copper(I) hexafluoridophosphate, [Cu(CH3 CN)(C29 H45 P)]PF6, 4, [2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ](perchlorato‐κ O )copper(I), [Cu(ClO4 )(C29 H45 P)], 5, and di‐μ‐thiocyanato‐κ 2 S : N ;κ 2 N : S ‐bis{[2‐(di‐ tert ‐butylphosphanyl)‐2′, 4′, 6′‐triisopropylbiphenyl‐κ P ]copper(I)}, [Cu2 (NCS)2 (C29 H45 P)2 ], 6 . Iodide complex 3 shows significant Cu I –arene interactions, in contrast to its chloride 1 and bromide 2 counterparts, which is attributed to the weaker interaction between the iodide ion and the Cu I centre. When replacing iodide with an acetonitrile (in 4 ) or perchlorate (in 5 ) ligand, the reduced interaction between the Cu I atom and the ancillary ligand results in stronger Cu I –arene interactions. No Cu I –arene interactions are observed in dimer 6, due to the tricoordinated Cu I centre having sufficient electron density from the coordinated ligands.